A transparent polycrystalline alumina super wear-resistant diamond glaze tile and preparation method thereof

By introducing transparent polycrystalline alumina particles into the glaze layer on the surface of the ceramic tile and adjusting their size and addition amount, the problems of poor wear resistance and poor decorative properties of the glaze layer on the surface of the ceramic tile are solved, and a combination of high wear resistance and good decorative properties are achieved.

CN119306471BActive Publication Date: 2025-03-25GUANGDONG DEER NEW MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411856005.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The glaze layer on the surface of the existing ceramic tile has poor wear resistance and poor decorative properties. Traditional methods can easily lead to a decrease in wear resistance or affect color when increasing the crystallization amount of the glaze layer surface or introducing wear-resistant components.

Method used

Transparent polycrystalline alumina is used as a wear-resistant component. By introducing transparent polycrystalline alumina particles into the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and controlling their particle size and addition amount, ensuring that the particles are retained during the polishing process, avoiding a decrease in wear resistance, and maintaining good light transmittance and color.

Benefits of technology

It effectively improves the hardness and wear resistance of the glaze layer on the surface of the ceramic tile, while maintaining good light transmittance and decorativeness, making the ceramic tile have high wear resistance and diamond-like transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306471B_ABST
    Figure CN119306471B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of ceramic tiles, and specifically discloses a transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile and a preparation method thereof, comprising a body layer, a bottom glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer from bottom to top; by weight, the raw material components of the transparent polycrystalline alumina super wear-resistant diamond glaze layer include: 25-40 parts of potassium feldspar, 12-25 parts of sodium feldspar, 5-15 parts of wollastonite, 5-15 parts of kaolin, 3-15 parts of quartz, 4-20 parts of transparent polycrystalline alumina, and 8-25 parts of wear-resistant frit, thereby ensuring that the ceramic tile product can maintain hardness and wear resistance during use. In addition, the transparent polycrystalline alumina has good light transmittance, good transparency, does not affect the color of the inkjet pattern, and while increasing the hardness and wear resistance of the surface glaze layer, ensures that the surface glaze layer has good light transmittance, thereby ensuring that the ceramic tile has good color and decorativeness as much as possible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic tiles, in particular to a transparent polycrystalline alumina super-wear-resistant diamond glaze ceramic tile and a preparation method thereof. Background Art

[0002] Floor tiles have been widely used in home and engineering decoration because of their advantages of good decorative effect, long service life, reasonable price, good flatness, and convenient paving. Wear resistance is an important property of tiles. Poor wear resistance will cause the product to change color, glossiness change, anti-fouling performance decrease, anti-slip performance change and other problems after a period of use, which directly affects the decorative effect and service life of the product. Therefore, the wear resistance of tiles has always been a concern of the industry and users. At present, decorative tiles and rock slabs are generally composed of green body, base glaze, pattern layer, and glaze. The physical and chemical properties of glaze directly affect the surface performance of the product. Therefore, the performance of the surface glaze layer is the key factor in determining the surface hardness and wear resistance of the tile.

[0003] The Chinese invention patent with publication number CN116023031A has a scheme of regulating the glaze composition and the firing process of ceramic tiles so that a large amount of cordierite crystals are precipitated in the glaze layer on the surface of the ceramic tile sample, thereby improving the hardness and wear resistance of the ceramic tile surface. However, increasing the amount of crystal precipitation on the surface of the glaze layer is not ideal for improving the wear resistance of the surface of the polished glazed ceramic tile. This is because during the firing process of the ceramic tile, impurities and defects are prone to appear on the surface of the glaze layer, and the energy required to form crystal nuclei at these defects is small. Therefore, the crystals precipitated in the glaze layer are often concentrated on the surface, and the preparation of polished glazed ceramic tiles requires polishing of the surface to ensure that the ceramic tile products have good decorative and anti-fouling properties. This causes the crystals precipitated on the surface of the glaze layer to be lost in large quantities during the surface polishing process, making it difficult to exert their wear-resistant properties. In addition, excessive crystal precipitation in the surface glaze layer will also affect the light transmittance of the glaze layer, thereby affecting the color of the ceramic tile, and then affecting its decorative performance. Therefore, controlling the crystallization of the glaze layer on the surface of the ceramic tile cannot effectively improve the wear resistance of the ceramic tile.

[0004] In addition, introducing wear-resistant components into the glaze layer on the surface of ceramic tiles is also an important means to improve the wear resistance of ceramic tiles. However, most wear-resistant components will have an adverse effect on the color of ceramic tiles, resulting in poor decorative properties of ceramic tiles. For example, the Chinese invention patent with publication number CN117843384A discloses a super non-slip and super wear-resistant ceramic tile and its production process, which introduces silicon carbide nanofibers and boron nitride into the glaze layer to improve the wear resistance of ceramic tiles. Although high-purity silicon carbide is a colorless and transparent crystal, it is relatively expensive and is not suitable for the field of building ceramic materials. And the silicon carbide that is currently widely used is mostly black. Although the Vickers hardness of this material is as high as 22GPa, the black silicon carbide will affect the color of the ceramic tile after being added to the glaze layer, thereby causing its decorative properties to deteriorate.

[0005] At the same time, a Chinese invention patent with publication number CN115368167A discloses a wear-resistant glazed tile and a preparation method thereof. The patent uses single-crystal alumina as a wear-resistant dry particle, and mixes the single-crystal alumina with a suspending agent to prepare a wear-resistant dry particle layer, and then applies an anti-fouling protective glaze on the surface of the wear-resistant dry particle layer. Although the patent introduces single-crystal alumina as a wear-resistant component that has little effect on the color of the tile into the tile, a protective glaze layer is then applied to the surface of the wear-resistant dry particle layer, which makes it difficult for the wear-resistant component added to the tile to play a role. Therefore, this solution is difficult to improve the hardness and wear resistance of the surface glaze layer. In addition, single-crystal alumina is expensive and difficult to crush, so the use of single-crystal alumina in building ceramics has no economic value. Summary of the invention

[0006] In order to overcome the defects of the prior art, the present invention provides a transparent polycrystalline alumina super wear-resistant diamond glaze tile and a preparation method thereof to solve the problems of poor wear resistance of the existing tile surface glaze layer and poor decorative properties of the tile.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] The first scheme of the present invention provides a transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile, comprising from bottom to top a body layer, a base glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer;

[0009] By weight, the raw material components of the transparent polycrystalline alumina super-wear-resistant diamond glaze layer include: 25-40 parts of potassium feldspar, 12-25 parts of sodium feldspar, 5-15 parts of wollastonite, 5-15 parts of kaolin, 3-15 parts of quartz, 4-20 parts of transparent polycrystalline alumina, and 8-25 parts of wear-resistant frit.

[0010] The scheme of the present invention is as follows:

[0011] The present invention introduces transparent polycrystalline alumina as a wear-resistant component into a transparent polycrystalline alumina super wear-resistant diamond glaze layer (hereinafter referred to as the surface glaze layer). The transparent polycrystalline alumina has high hardness (Vickers hardness is greater than 16 GPa). Compared with the traditional process of increasing the amount of crystallization on the surface of the glaze layer to improve the wear resistance of tiles, the added transparent polycrystalline alumina particles are evenly distributed in the surface glaze layer. Therefore, this solution can effectively avoid the problem of reduced wear resistance caused by polishing, thereby ensuring that the tile product can maintain hardness and wear resistance during use. In addition to having a high hardness, transparent polycrystalline alumina also has good light transmittance and good transparency, and does not affect the color of the inkjet pattern. While increasing the hardness and wear resistance of the surface glaze layer, it can ensure that the surface glaze layer has good light transmittance, thereby ensuring that the tile has good color and decorative properties as much as possible, so that the product is as bright as a diamond and has high wear resistance.

[0012] In addition, although the use of transparent polycrystalline alumina particles as the wear-resistant component of the ceramic tile surface glaze layer can improve the wear resistance of the surface glaze layer, the thermal expansion coefficient of polycrystalline alumina is higher than that of the traditional ceramic tile surface glaze layer, which may lead to the formation of microcracks on the ceramic tile surface, and then lead to the deterioration of the antifouling and decorative properties of the ceramic tile surface. Therefore, the introduction of potassium feldspar and sodium feldspar can be used to regulate the thermal expansion coefficient of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, thereby ensuring that the thermal expansion coefficient of the transparent polycrystalline alumina super wear-resistant diamond glaze layer substrate matches that of the transparent polycrystalline alumina.

[0013] Preferably, the average particle size of the transparent polycrystalline alumina is 30-100 μm. The transparent polycrystalline alumina within this average particle size range can ensure that after polishing the transparent polycrystalline alumina super wear-resistant diamond glaze layer of the tile, the transparent polycrystalline alumina with an appropriate particle size can be retained, while avoiding the loss caused by the excessive average particle size of the transparent polycrystalline alumina, so that the transparent polycrystalline alumina super wear-resistant diamond glaze layer still has good wear resistance.

[0014] For further explanation, see the attached Figure 1-2 As shown, the transparent polycrystalline alumina of the technical solution uses the transparent polycrystalline alumina tube for waste high-pressure sodium lamps and its processing waste as raw materials, and further processes to obtain transparent polycrystalline alumina with an average particle size of 30-100μm, specifically sintered in a hydrogen atmosphere at a temperature higher than 1800°C. The transparent polycrystalline alumina prepared by this process has the characteristics of being dense, having a large grain size, having a thin grain boundary thickness and having fewer defects at the grain boundary. The surface grain morphology of the transparent polycrystalline alumina is shown in the attached Figure 3 As shown, it has good light transmittance and good transparency, and does not affect the color of the inkjet pattern. While increasing the hardness and wear resistance of the surface glaze layer, it can also make the surface glaze layer have good light transmittance, thereby ensuring that the tiles have good color and decorative properties as much as possible.

[0015] Transparent polycrystalline alumina tubes are the most important components of high-pressure sodium lamps, and the demand is huge. The unqualified transparent polycrystalline alumina tubes produced during the production process and the waste materials in the later processing are currently mainly disposed of by landfill. By comprehensively utilizing the waste transparent polycrystalline alumina tubes and processing waste resources, the environmental governance pressure of manufacturers can also be reduced.

[0016] Preferably, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 50-100 μm. A glaze layer that is too thick will affect the transparency of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, while the transparent polycrystalline alumina super wear-resistant diamond glaze layer within this thickness range can ensure that the transparent polycrystalline alumina super wear-resistant diamond glaze layer has good transparency, thereby making the surface of the tile present better color and texture; at the same time, in combination with the above-mentioned transparent polycrystalline alumina with an average particle size of 30-100 μm, the transparent polycrystalline alumina super wear-resistant diamond glaze layer achieves better wear resistance (a glaze layer that is too thick will cover the transparent polycrystalline alumina particles, resulting in a decrease in wear resistance; a glaze layer that is too thin will cause the transparent polycrystalline alumina particles to be overly exposed, resulting in the loss of transparent polycrystalline alumina particles during glazing).

[0017] Preferably, the chemical composition of the wear-resistant frit includes, by weight percentage: SiO2 50-70%, Al2O3 0-10%, first metal oxide 20-40%, second metal oxide 0-3%;

[0018] The first metal oxide is a mixture of CaO, MgO, ZnO, BaO and SrO;

[0019] The second metal oxide is a mixture of Na2O and K2O.

[0020] Preferably, the raw material components of the green body layer include, by weight: 1-5 parts of black mud, 1-8 parts of mixed mud, 40-55 parts of kaolin, 12-25 parts of high temperature sand, 5-15 parts of feldspar, 3-8 parts of talc, 1-5 parts of bauxite, and 1-5 parts of green body additives. The green body additives can be selected from one or more of water reducers and reinforcing agents.

[0021] Preferably, the raw material components of the base glaze layer include, by weight: 30-45 parts of quartz, 12-18 parts of potassium feldspar, 3-10 parts of sodium feldspar, 3-10 parts of talc, 1-5 parts of wollastonite, 1-5 parts of dolomite, 3-10 parts of kaolin, and 1-5 parts of base glaze additives. The base glaze additives can be selected from one or more of water reducers and methyl cellulose.

[0022] In addition, the present invention adjusts the composition of the ceramic tile body layer, the base glaze layer and the surface glaze layer so that the thermal expansion coefficients of the various components of the ceramic tile are matched, so that the thermal expansion coefficients of the above three show a gradient change, so that the ceramic tile has good stability as a whole while taking into account the matching of the thermal expansion coefficients of the surface glaze layer matrix and the transparent polycrystalline alumina.

[0023] The second solution of the present invention is to provide a method for preparing a transparent polycrystalline alumina super wear-resistant diamond glaze tile, the preparation method is used to prepare the above-mentioned transparent polycrystalline alumina super wear-resistant diamond glaze tile, the preparation method comprises the following steps:

[0024] (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are batched and fully mixed, and melted into glass liquid at 1500-1650°C. The glass liquid is poured into water, quenched, and crushed into frit particles;

[0025] (2) mixing the frit particles with other raw materials of a transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain a transparent polycrystalline alumina super wear-resistant diamond glaze;

[0026] (3) applying a base glaze, inkjet printing a pattern, and applying a transparent polycrystalline alumina super wear-resistant diamond glaze on the body in sequence, so that the transparent polycrystalline alumina super wear-resistant diamond glaze covers the pattern; drying, firing in a kiln, and polishing to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze tile.

[0027] Preferably, the firing curve of the kiln firing is: heating from room temperature to 1190-1220°C at a heating rate of 10°C / min, keeping at this temperature for 5-20 minutes, and finally cooling naturally after leaving the kiln.

[0028] Preferably, the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile surface Vickers hardness ≥ 7GPa, the wear resistance reaches 6000 revolutions level 4, and the anti-fouling level reaches level 5.

[0029] The present invention has at least one of the following beneficial effects:

[0030] (1) The present invention introduces transparent polycrystalline alumina as a wear-resistant component into the transparent polycrystalline alumina super wear-resistant diamond glaze layer. The transparent polycrystalline alumina has high hardness. Compared with the traditional process of increasing the amount of crystallization on the surface of the glaze layer to improve the wear resistance of the tile, the added transparent polycrystalline alumina particles are evenly distributed in the surface glaze layer. Therefore, this solution can effectively avoid the problem of reduced wear resistance caused by polishing, thereby ensuring that the tile product can maintain hardness and wear resistance during use. In addition to having a high hardness, transparent polycrystalline alumina also has good light transmittance and good transparency. It does not affect the color of the inkjet pattern layer. While increasing the hardness and wear resistance of the surface glaze layer, it can ensure that the surface glaze layer has good light transmittance, thereby ensuring that the tile has good color and decorative properties as much as possible, making the product as bright as a diamond and highly wear-resistant.

[0031] (2) By adjusting the particle size and addition amount of transparent polycrystalline alumina, the hardness and wear resistance of the surface glaze layer can be improved while ensuring that the surface glaze layer has good light transmittance, thereby ensuring that the tile product has good color and decorative properties as much as possible. The transparent polycrystalline alumina super wear-resistant diamond glaze tile surface Vickers hardness ≥ 7GPa, wear resistance reaches 6000 revolutions 4 level, and anti-fouling level reaches 5 level.

[0032] (3) The present invention regulates the composition of the ceramic tile blank, the base glaze and the transparent polycrystalline alumina super wear-resistant diamond glaze layer, so that the thermal expansion coefficients of the above three show a gradient change, so as to ensure that the thermal expansion coefficients of the transparent polycrystalline alumina super wear-resistant diamond glaze layer matrix match the transparent polycrystalline alumina particles, and the overall stability of the ceramic tile is not affected. The thermal expansion coefficient of the ceramic tile blank of the present invention is 7.2*10 -6 1 / K, the expansion coefficient of the base glaze is 6.8*10 -6 1 / K The expansion coefficient of the glaze layer is 6.5*10 -6 1 / K, the expansion coefficient of transparent polycrystalline alumina is 8.0*10 -6 1 / K. The above expansion coefficient temperature range is 25-700℃. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Attached Figure 1 This is a photo of the processing waste of transparent polycrystalline alumina tube;

[0034] Attached Figure 2 The XRD test results of the processing waste of transparent polycrystalline alumina;

[0035] Attached Figure 3 This is a picture of the grain morphology on the surface of transparent polycrystalline alumina;

[0036] Attached Figure 4 This is a cross-sectional morphology diagram of the tile sample in Example 1;

[0037] Attached Figure 5 This is the element distribution diagram of the transparent polycrystalline alumina super wear-resistant diamond glaze layer of the tile sample in Example 1;

[0038] Attached Figure 6 The XRD test results of the transparent polycrystalline alumina super wear-resistant diamond glaze layer of the tile sample in Example 1;

[0039] Attached Figure 7 This is an optical microscope observation picture of the surface of the tile sample in Example 2;

[0040] Attached Figure 8 This is an optical microscope observation picture of the surface of the tile sample in Example 3;

[0041] Attached Fig. 9 The element composition analysis results of the glaze layer at the fracture of the ceramic tile sample in Example 4;

[0042] Attached Fig.10 is a cross-sectional morphology diagram of the tile sample in Example 5;

[0043] Attached Fig.11 This is a cross-sectional morphology of the tile sample in Comparative Example 2;

[0044] Attached Fig.12 This is an optical microscope observation picture of the surface of the tile sample in Comparative Example 2;

[0045] Attached Fig.13 This is a cross-sectional morphology of the tile sample in Comparative Example 3;

[0046] Attached Fig.14 This is a cross-sectional morphology of the tile sample in Comparative Example 4;

[0047] Attached Fig.15 This is an optical microscope observation picture of the surface of the tile sample in Comparative Example 4;

[0048] Attached Fig.16 This is the cross-sectional morphology of the tile sample in Comparative Example 5. DETAILED DESCRIPTION

[0049] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0050] In the embodiments and comparative examples of the present invention, by weight,

[0051] The raw material components of the green body layer include: 3 parts of black mud, 5 parts of mixed mud, 48 parts of kaolin, 18 parts of high-temperature sand, 10 parts of feldspar, 5 parts of talc, 3 parts of bauxite, and 3 parts of green body additives.

[0052] The raw material components of the base glaze layer include: 40 parts of quartz, 15 parts of potassium feldspar, 7 parts of sodium feldspar, 6 parts of talc, 3 parts of wollastonite, 3 parts of dolomite, 7 parts of kaolin and 3 parts of base glaze additive.

[0053] Example 1

[0054] A transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer;

[0055] The raw material components of the transparent polycrystalline alumina super wear-resistant diamond glaze layer include, by weight: 40 parts of potassium feldspar, 12 parts of sodium feldspar, 11 parts of wollastonite, 5 parts of kaolin, 5 parts of quartz, 7 parts of transparent polycrystalline alumina, and 20 parts of wear-resistant frit.

[0056] Wherein, the average particle size of transparent polycrystalline alumina is 100 μm;

[0057] The chemical composition of the wear-resistant frit includes, by weight percentage: SiO2 60%, Al2O 35%, first metal oxide 33%, second metal oxide 2%;

[0058] The first metal oxide is a mixture of CaO, MgO, ZnO, BaO and SrO; and the second metal oxide is a mixture of Na2O and K2O.

[0059] The preparation method of the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises the following steps:

[0060] (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are mixed and fully melted into glass liquid at 1500°C, and the glass liquid is poured into water, quenched, crushed and passed through a 100-mesh sieve to form frit particles;

[0061] (2) mixing the frit particles with other raw materials of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze;

[0062] (3) Apply base glaze, inkjet print patterns, and transparent polycrystalline alumina super wear-resistant diamond glaze to the body in sequence, so that the transparent polycrystalline alumina super wear-resistant diamond glaze covers the pattern, and then dry and fire in a kiln. The firing curve for firing in the kiln is: heating from room temperature to 1190°C at a heating rate of 10°C / min, keeping at this temperature for 5 minutes, and finally taking out of the kiln for natural cooling and polishing to obtain transparent polycrystalline alumina super wear-resistant diamond glaze tiles. At this time, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 50μm.

[0063] Example 2

[0064] A transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer;

[0065] The raw material components of the transparent polycrystalline alumina super wear-resistant diamond glaze layer include, by weight: 32 parts of potassium feldspar, 20 parts of sodium feldspar, 5 parts of wollastonite, 12 parts of kaolin, 7 parts of quartz, 4 parts of transparent polycrystalline alumina, and 20 parts of wear-resistant frit.

[0066] Wherein, the average particle size of transparent polycrystalline alumina is 100 μm;

[0067] The chemical composition of the wear-resistant frit includes, by weight percentage: SiO2 60%, Al2O 35%, first metal oxide 33%, second metal oxide 2%;

[0068] The first metal oxide is a mixture of CaO, MgO, ZnO, BaO and SrO; and the second metal oxide is a mixture of Na2O and K2O.

[0069] The preparation method of the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises the following steps:

[0070] (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are mixed and fully melted into glass liquid at 1500°C, and the glass liquid is poured into water, quenched, crushed and passed through a 100-mesh sieve to form frit particles;

[0071] (2) mixing the frit particles with other raw materials of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze;

[0072] (3) Apply base glaze, inkjet print patterns, and ultra-transparent polycrystalline alumina ultra-wear-resistant diamond glaze to the body in sequence, so that the transparent polycrystalline alumina ultra-wear-resistant diamond glaze covers the pattern. After drying and firing in a kiln, the firing curve for firing in the kiln is as follows: heating from room temperature to 1190°C at a heating rate of 10°C / min, keeping at this temperature for 5 minutes, and finally taking out of the kiln to cool naturally and polish to obtain ultra-wear-resistant tiles. At this time, the average thickness of the transparent polycrystalline alumina ultra-wear-resistant diamond glaze layer is 50 μm.

[0073] Example 3

[0074] A transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer;

[0075] The raw material components of the transparent polycrystalline alumina super wear-resistant diamond glaze layer include, by weight: 25 parts of potassium feldspar, 25 parts of sodium feldspar, 13 parts of wollastonite, 5 parts of kaolin, 15 parts of quartz, 7 parts of transparent polycrystalline alumina, and 10 parts of wear-resistant frit.

[0076] Among them, the average particle size of transparent polycrystalline alumina is 30 μm;

[0077] The chemical composition of the wear-resistant frit includes, by weight percentage: SiO2 60%, Al2O 35%, first metal oxide 33%, second metal oxide 2%;

[0078] The first metal oxide is a mixture of CaO, MgO, ZnO, BaO and SrO; and the second metal oxide is a mixture of Na2O and K2O.

[0079] The preparation method of the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises the following steps:

[0080] (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are mixed and fully melted into glass liquid at 1500°C, and the glass liquid is poured into water, quenched, crushed and passed through a 100-mesh sieve to form frit particles;

[0081] (2) mixing the frit particles with other raw materials of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze;

[0082] (3) Apply base glaze, inkjet print pattern and transparent polycrystalline alumina super wear-resistant diamond glaze to the body in sequence, so that the transparent polycrystalline alumina super wear-resistant diamond glaze covers the pattern, dry and put into kiln for firing. The firing curve of the kiln firing is: heating from room temperature to 1190°C at a heating rate of 10°C / min, keeping at this temperature for 5 minutes, and finally taking out of the kiln for natural cooling and polishing to obtain transparent polycrystalline alumina super wear-resistant diamond glaze tiles. At this time, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 100μm.

[0083] Example 4

[0084] A transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer;

[0085] By weight, the raw material components of the transparent polycrystalline alumina super wear-resistant diamond glaze layer include: 30 parts of potassium feldspar, 12 parts of sodium feldspar, 8 parts of wollastonite, 5 parts of kaolin, 5 parts of quartz, 15 parts of transparent polycrystalline alumina, and 25 parts of wear-resistant frit.

[0086] Wherein, the average particle size of transparent polycrystalline alumina is 100 μm;

[0087] The chemical composition of the wear-resistant frit includes, by weight percentage: SiO2 60%, Al2O 35%, first metal oxide 33%, second metal oxide 2%;

[0088] The first metal oxide is a mixture of CaO, MgO, ZnO, BaO and SrO; and the second metal oxide is a mixture of Na2O and K2O.

[0089] The preparation method of the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises the following steps:

[0090] (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are mixed and fully melted into glass liquid at 1500°C, and the glass liquid is poured into water, quenched, crushed and passed through a 100-mesh sieve to form frit particles;

[0091] (2) mixing the frit particles with other raw materials of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze;

[0092] (3) Apply base glaze, inkjet print patterns, and transparent polycrystalline alumina super wear-resistant diamond glaze to the body in sequence, so that the transparent polycrystalline alumina super wear-resistant diamond glaze covers the pattern. After drying and firing in a kiln, the firing curve for firing in the kiln is as follows: heating from room temperature to 1190°C at a heating rate of 10°C / min, keeping at this temperature for 5 minutes, and finally taking out of the kiln for natural cooling and polishing to obtain transparent polycrystalline alumina super wear-resistant diamond glaze tiles. At this time, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 60μm.

[0093] Example 5

[0094] A transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises, from bottom to top, a body layer, a base glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer;

[0095] The raw material components of the transparent polycrystalline alumina super wear-resistant diamond glaze layer include, by weight: 25 parts of potassium feldspar, 12 parts of sodium feldspar, 15 parts of wollastonite, 15 parts of kaolin, 3 parts of quartz, 20 parts of transparent polycrystalline alumina, and 8 parts of wear-resistant frit.

[0096] Wherein, the average particle size of transparent polycrystalline alumina is 100 μm;

[0097] The chemical composition of the wear-resistant frit includes, by weight percentage: SiO2 60%, Al2O 35%, first metal oxide 33%, second metal oxide 2%;

[0098] The first metal oxide is a mixture of CaO, MgO, ZnO, BaO and SrO; and the second metal oxide is a mixture of Na2O and K2O.

[0099] The preparation method of the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile comprises the following steps:

[0100] (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are mixed and fully melted into glass liquid at 1650°C, and the glass liquid is poured into water, quenched, crushed and passed through a 100-mesh sieve to form frit particles;

[0101] (2) mixing the frit particles with other raw materials of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze;

[0102] (3) Apply base glaze, inkjet print patterns, and transparent polycrystalline alumina super wear-resistant diamond glaze to the body in sequence, so that the transparent polycrystalline alumina super wear-resistant diamond glaze covers the pattern, and then dry and fire in a kiln. The firing curve for firing in the kiln is: heating from room temperature to 1220°C at a heating rate of 10°C / min, keeping at this temperature for 20 minutes, and finally taking out of the kiln for natural cooling and polishing to obtain transparent polycrystalline alumina super wear-resistant diamond glaze tiles. At this time, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 100 μm.

[0103] Comparative Example 1

[0104] The only difference between Comparative Example 1 and Example 2 is that the content of transparent polycrystalline alumina in Comparative Example 1 is too small, and the types and addition amounts of other raw materials and the preparation method of the ceramic tile are consistent with those in Example 2.

[0105] In Comparative Example 1, the raw material components of the surface glaze layer include, by weight: 32 parts of potassium feldspar, 20 parts of sodium feldspar, 5 parts of wollastonite, 12 parts of kaolin, 7 parts of quartz, 1 part of transparent polycrystalline alumina, and 20 parts of wear-resistant frit.

[0106] Comparative Example 2

[0107] The only difference between Comparative Example 2 and Example 2 is that the content of transparent polycrystalline alumina in Comparative Example 2 is too high, and the types and addition amounts of other raw materials and the preparation method of the ceramic tile are consistent with those in Example 2.

[0108] In Comparative Example 2, the raw material components of the surface glaze layer include, by weight: 32 parts of potassium feldspar, 20 parts of sodium feldspar, 5 parts of wollastonite, 12 parts of kaolin, 7 parts of quartz, 25 parts of transparent polycrystalline alumina, and 20 parts of wear-resistant frit.

[0109] Comparative Example 3

[0110] The difference between Comparative Example 3 and Example 3 is that in the preparation method of transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tiles, a layer of protective glaze is applied on the upper surface of the transparent polycrystalline alumina super wear-resistant diamond glaze layer in Comparative Example 3.

[0111] The method for preparing the ceramic tile in Comparative Example 3 comprises the following steps:

[0112] (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are mixed and fully melted into glass liquid at 1500°C, and the glass liquid is poured into water, quenched, crushed and passed through a 100-mesh sieve to form frit particles;

[0113] (2) mixing the frit particles with other raw materials of the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze;

[0114] (3) Apply base glaze, inkjet print pattern, transparent polycrystalline alumina super wear-resistant diamond glaze and protective glaze on the body in sequence, so that the transparent polycrystalline alumina super wear-resistant diamond glaze covers the pattern, dry and put into kiln for firing. The firing curve of the kiln firing is: heating from room temperature to 1190°C at a heating rate of 10°C / min, keeping at this temperature for 5 minutes, and finally taking out of the kiln for natural cooling and polishing to obtain transparent polycrystalline alumina super wear-resistant diamond glaze tiles. At this time, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 100μm.

[0115] The chemical composition of the protective glaze by weight percentage is: SiO2 55%, Al2O3 18%, K2O 3%, Na2O 3%, CaO 4%, MgO 2%, SrO 2%, ZnO 4%, ZrO2 3%, SiO2 1%, Al2O3 2%, K2O 2%, Na2O 1%.

[0116] Comparative Example 4

[0117] The only difference between Comparative Example 4 and Example 3 is that the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer in Comparative Example 4 is too large, which is 160 μm, and the types and addition amounts of other raw materials and the preparation method of the ceramic tile are consistent with those in Example 3.

[0118] Comparative Example 5

[0119] The only difference between Comparative Example 5 and Example 3 is that the average particle size of the transparent polycrystalline alumina in Comparative Example 5 is too large, which is 150 μm, and the types and addition amounts of other raw materials and the preparation method of the ceramic tile are consistent with those in Example 3.

[0120] Comparative Example 6

[0121] The only difference between Comparative Example 6 and Example 3 is that the average particle size of the transparent polycrystalline alumina in Comparative Example 6 is too small, which is 10 μm. The types and addition amounts of other raw materials and the preparation method of the ceramic tile are consistent with those in Example 3.

[0122] Comparative Example 7

[0123] The only difference between Comparative Example 7 and Example 3 is that in Comparative Example 7, the transparent polycrystalline alumina with an average particle size of 30 μm is replaced by single crystal alumina with an average particle size of 80 μm, and the types and addition amounts of other raw materials and the preparation method of the ceramic tile are consistent with those in Example 3.

[0124] The performance of the tiles corresponding to Examples 1-5 and Comparative Examples 1-7 is tested, and the results are shown in the following table:

[0125]

[0126] From the test results we can see that:

[0127] Embodiments 1-5 of the present invention improve the hardness, wear resistance and antifouling performance of the glaze layer on the surface of the tile by controlling the raw material composition of the transparent polycrystalline alumina super wear-resistant diamond glaze layer and using transparent polycrystalline alumina particles as the wear-resistant component; and the surface grain morphology of the transparent polycrystalline alumina is as shown in the attached Figure 3 As shown, the transparent polycrystalline alumina also has good light transmittance and good transparency, which makes the transparent polycrystalline alumina super wear-resistant diamond glaze layer have good transparency and does not affect the color of the inkjet pattern layer, thereby not affecting the color and texture of the tile, that is, it does not affect the decorativeness of the tile.

[0128] The surface glaze layer of the transparent polycrystalline alumina super wear-resistant diamond glaze tile sample prepared in Example 1 was characterized by SEM and XRD. The test results are shown in the attached figure. Figure 4 , Attachment Figure 5 And attached Figure 6 As shown. Figure 4 It can be seen from the figure that the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer prepared in this embodiment is 50 μm. Figure 5 From the test results of the distribution of elements on the surface of the polished ceramic tile samples, it can be seen that the transparent polycrystalline alumina particles are evenly dispersed in the transparent polycrystalline alumina super wear-resistant diamond glaze layer, and the ceramic tile samples still contain a large number of transparent polycrystalline alumina particles on the surface after polishing; Figure 6 It can be seen that by regulating the raw material composition of the transparent polycrystalline alumina super wear-resistant diamond glaze layer and the firing temperature of the tile, crystals such as potassium feldspar and calcium feldspar are precipitated in the glaze layer, which will further improve the wear resistance of the surface glaze layer.

[0129] After polishing, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 50 μm. Figure 7 This is an optical microscope observation picture of the surface of the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile corresponding to this embodiment. It can be seen from the picture that the transparent polycrystalline alumina super wear-resistant diamond glaze layer has good transparency and high density, and does not affect the color and texture of the ceramic tile surface.

[0130] After polishing, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 100 μm. Figure 8 The optical microscope observation picture of the surface of the transparent polycrystalline alumina super wear-resistant diamond glaze tile sample corresponding to this embodiment. Figure 7 and attached Figure 8 , the thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer increases, but the glaze layer still has good transparency (such as the attached Figure 8 As shown), it does not affect the color and texture of the tile surface.

[0131] In Example 4, the transparent polycrystalline alumina super wear-resistant diamond glaze layer has an increased transparent polycrystalline alumina content, and the wear resistance and hardness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer are further improved. Subsequently, the element analysis of the fracture of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is performed, and the test results are shown in the attached figure. Fig. 9 As shown in the figure, it can be seen that the added transparent polycrystalline alumina is still evenly distributed perpendicular to the glaze surface, which makes the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile prepared by this scheme still have good wear resistance even after surface polishing; and after the ceramic tile sample is polished, the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 60μm, and the glaze layer has good transparency and does not affect the color and texture of the transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile.

[0132] After polishing in Example 5, the cross-sectional SEM characterization results of the transparent polycrystalline alumina super wear-resistant diamond glaze layer are shown in the attached figure. Fig.10 As shown in the figure, it can be seen that the average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 100 μm, and as the content of transparent polycrystalline alumina increases, the hardness of the glaze layer on the surface of the transparent polycrystalline alumina super wear-resistant diamond glaze tile increases.

[0133] In Comparative Example 1, since the amount of transparent polycrystalline alumina added is too small, compared with Example 2, the hardness and wear resistance of the surface glaze layer of the tile prepared in Comparative Example 1 are significantly reduced.

[0134] The SEM characterization results of the tiles prepared in Comparative Example 2 are shown in the attached Fig.11 As shown in FIG. 1 , after polishing, the average thickness of the glaze layer on the surface of the tile is 100 μm. Compared with Example 2, due to the excessive addition of transparent polycrystalline alumina, the light transmittance of the glaze layer on the surface of the tile sample is significantly reduced, and the porosity is significantly increased (as shown in FIG. Fig.11 , 12 As shown), this will lead to the deterioration of the decorative properties of the tiles and the reduction of their anti-fouling performance.

[0135] The SEM characterization results of the tiles prepared in Comparative Example 3 are shown in the attached Fig.13 As shown in the figure, after polishing, the average thickness of the surface glaze layer of the tile is 160 μm. Compared with Example 3, the hardness and wear resistance of the surface glaze layer of Comparative Example 3 are reduced. From the test results, it can be concluded that the addition position of transparent polycrystalline alumina is particularly important. When transparent polycrystalline alumina is added to the non-surface glaze layer, it does not exert its high hardness characteristics and cannot improve the hardness and wear resistance of the surface glaze layer of the tile sample. In addition, since a protective glaze layer is applied twice on the surface of the transparent polycrystalline alumina super-wear-resistant diamond glaze layer, the inkjet-printed pattern is covered by a thicker glaze layer, which seriously affects the color development and decorative performance of the tile.

[0136] The SEM characterization results of the tiles prepared in Comparative Example 4 are shown in the attached Fig.14 As shown in the figure, after polishing, the average thickness of the surface glaze layer of the tile is 160 μm. Compared with Example 3, the surface glaze layer is too thick, which causes the inkjet printed pattern to be covered by the thicker glaze layer. Fig.15 This is an optical microscope observation picture of the surface of the ceramic tile produced in this comparison ratio. It can be seen from the picture that a glaze layer that is too thick will also lead to an increase in the discharge path of the pores contained therein. It is difficult for the gas to rise to the surface of the glaze layer in time to be discharged, resulting in an increase in porosity, which seriously reduces the anti-fouling performance, color development and decorative performance of the ceramic tile.

[0137] For the ceramic tile prepared in Example 5, the test results show that the particle size of transparent polycrystalline alumina has some influence on the antifouling performance of the ceramic tile surface glaze layer. Since there is a large difference in thermal expansion coefficient between the transparent polycrystalline alumina and the surface glaze layer matrix, if the transparent polycrystalline alumina particles are too large, micro cracks will be formed in the surface glaze layer due to excessive internal stress. Fig.16 As shown, this will lead to a decrease in the density of the glaze layer, thereby reducing the anti-fouling and wear resistance of the tile surface.

[0138] For the tiles prepared in Comparative Example 6, it can be concluded from the test results that if the transparent polycrystalline alumina particles are too small, the wear resistance of the glaze layer on the surface of the tile will be reduced, and the hardness of the glaze layer on the surface of the tile will also be reduced.

[0139] From the test results, it can be seen that the effect of using single crystal alumina as raw material to improve the wear resistance of the tile surface is inferior to that of transparent polycrystalline alumina, and the anti-fouling performance of the tile samples prepared by adding single crystal alumina is poor. This is because the physical properties of single crystal alumina are anisotropic, which leads to different changes in the single crystal alumina in various directions during the preparation process of the tile samples, resulting in a decrease in the density of the surface glaze layer and an increase in microcracks. Therefore, using single crystal alumina as the wear-resistant component of the tile surface glaze layer will not only lead to a decrease in the wear resistance and anti-fouling performance of the surface glaze layer, but also affect the decorativeness of the tile.

[0140] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A transparent polycrystalline alumina super wear-resistant diamond glaze tile, characterized by: It consists of a body layer, a base glaze layer, a pattern layer and a transparent polycrystalline alumina super wear-resistant diamond glaze layer from bottom to top; The raw material components of the transparent polycrystalline alumina super wear-resistant diamond glaze layer are as follows: 25-40 parts of potassium feldspar, 12-25 parts of sodium feldspar, 5-15 parts of wollastonite, 5-15 parts of kaolin, 3-15 parts of quartz, 4-20 parts of transparent polycrystalline alumina, and 8-25 parts of wear-resistant frit by weight. The average particle size of the transparent polycrystalline alumina is 30-100 μm; The average thickness of the transparent polycrystalline alumina super wear-resistant diamond glaze layer is 50-100 μm; The chemical composition of the wear-resistant frit includes, by weight percentage: SiO2 50-70%, Al2O3 0-10%, first metal oxide 20-40%, second metal oxide 0-3%; The first metal oxide is a mixture of CaO, MgO, ZnO, BaO and SrO; The second metal oxide is a mixture of Na2O and K2O.

2. A transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile according to claim 1, characterized in that: By weight, the raw material components of the green body layer include: 1-5 parts of black mud, 1-8 parts of mixed mud, 40-55 parts of kaolin, 12-25 parts of high-temperature sand, 5-15 parts of feldspar, 3-8 parts of talc, 1-5 parts of bauxite, and 1-5 parts of green body additives.

3. The transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile according to claim 1, characterized in that: The raw material components of the base glaze layer include, by weight: 30-45 parts of quartz, 12-18 parts of potassium feldspar, 3-10 parts of sodium feldspar, 3-10 parts of talc, 1-5 parts of wollastonite, 1-5 parts of dolomite, 3-10 parts of kaolin, and 1-5 parts of base glaze additive.

4. A method for preparing transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile, characterized in that: The preparation method is used to prepare a transparent polycrystalline alumina super wear-resistant diamond glaze tile according to any one of claims 1 to 3, and the preparation method comprises the following steps: (1) According to the chemical composition of the wear-resistant frit, the raw materials containing the corresponding ingredients are batched and fully mixed, and melted into glass liquid at 1500-1650°C. The glass liquid is poured into water, quenched, and crushed into frit particles; (2) mixing the frit particles with other raw materials of a transparent polycrystalline alumina super wear-resistant diamond glaze layer, and performing wet ball milling to obtain a transparent polycrystalline alumina super wear-resistant diamond glaze; (3) applying a base glaze, inkjet printing a pattern, and applying a transparent polycrystalline alumina super wear-resistant diamond glaze on the body in sequence, so that the transparent polycrystalline alumina super wear-resistant diamond glaze covers the pattern; drying, firing in a kiln, and polishing to obtain the transparent polycrystalline alumina super wear-resistant diamond glaze tile.

5. The method for preparing transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile according to claim 4, characterized in that: The firing curve of the kiln firing is: heating from room temperature to 1190-1220° C. at a heating rate of 10° C. / min, keeping at this temperature for 5-20 minutes, and finally cooling naturally after leaving the kiln.

6. The method for preparing transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile according to claim 4, characterized in that: The transparent polycrystalline alumina super wear-resistant diamond glaze ceramic tile has a surface Vickers hardness of ≥7GPa, a wear resistance of 6000 revolutions and a level 4 anti-fouling level of 5.

Citation Information

Patent Citations

  • Wear-resistant glazed brick and preparation method thereof

    CN115368167A

  • Wear-resistant glazed tile glaze and preparation method thereof as well as glazed tile and preparation method thereof

    CN116023031A

  • Super-skid-resistant and super-wear-resistant ceramic tile and production process thereof

    CN117843384A

  • High-hardness super-wear-resistant fully-polished marble tile and preparation method thereof

    CN113968728A